Hydrogeological analysis of interflow with FEFLOW for a tailing dam – Arequipa - Contreras Gutiérrez, Efraín Jhiaromir (2022)
The development of this research project, aims to apply, validate and adapt the hydrogeological model with the commercial software FEFLOW 7.3, to predict streamlines through filtration rates, for the purpose of installing sub drains at the foot of the tailings dam, by discretizing the domain using the finite element technique. The input parameter to the model consists, with the Soil and Rock Mechanics Study, in the integration of the data from the meteorological stations provided by SENAMHI, with the Hydrological Study, obtaining the design intensities. The scenarios that arise in the model are for a return time of 500 years in a steady and transitory state. Without the installation of sub drains, filtrations were obtained from 1.9412e+5 m3/d, and with the installation of sub drains it drops to 44.34 m3/d, managing to demonstrate the proper functioning of the structure against recharges by installing sub drains at the foot of the tailings dam.